Clinical Performance Scores Are Independently Associated with the American Board of Anesthesiology Certification Examination Scores. (June 2016) - Baker, Keith; Sun, Huaping; Harman, Ann; Poon, K. Trudy; Rathmell, James P.
Abstract : BACKGROUND: It is unknown whether clinical performance during residency is related to the American Board of Anesthesiology (ABA) oral examination scores. We hypothesized that resident clinical performance would be independently associated with oral examination performance because the oral examination is designed to test for clinical judgment. METHOD: We determined clinical performance scores (Zrel ) during the final year of residency for all 124 Massachusetts General Hospital (MGH) anesthesia residents who graduated from 2009 to 2013. One hundred eleven graduates subsequently took the ABA written and oral examinations. We standardized each graduate's written examination score (ZPart 1 ) and oral examination score (ZPart 2 ) to the national average. Multiple linear regression analysis was used to determine the partial effects of MGH clinical performance scores and ABA written examination scores on ABA oral examination scores. RESULTS: MGH clinical performance scores (Zrel ) correlated with both ABA written examination scores (ZPart 1 ) ( r = 0.27; P = 0.0047) and with ABA oral examination scores (ZPart 2 ) ( r = 0.33; P = 0.0005). ABA written examination scores (ZPart 1 ) correlated with oral examination scores (ZPart 2 ) ( r = 0.46; P = 0.0001). Clinical performance scores (Zrel ) and ABA written examination scores (ZPart 1 ) independently accounted for 4.5% (95% confidence interval [CI], 0.5%–12.4%; P = 0.012) and 20.8% (95% CI, 8.0%–37.2%; P < 0.0001), respectively, of the variance in ABA oral examination scores (ZPart 2 ). CONCLUSIONS: Clinical performance scores and ABA written examination scores independently accounted for variance in ABA oral examination scores. Clinical performance scores are independently associated with the ABA oral examination scores.